Under the boardwalk [videorecording (DVD)] - Soren, David, 1973-; Scafaria, Lorene; Dobkin, David, 1969- (Paramount, 2023)
When timid Jersey crab Armen meets bold tourist sea crab, Ramona, it causes shell-shocking tension in the community. But when the duo is swept away by a storm, they embark on an epic journey to find a home. Their courage unites their families paving the way for great summers to come, Under the Boardwalk.